Effective Teacher Behaviors Evident in Successful Teachers of Students with Emotional and Behavioral Disorders - Austin, Vance L.; Barowsky, Ellis I.; Malow, Micheline S.; Gómez, Diane W. (Journal of the American Academy of Special Education Professionals, 2011)
Four highly qualified teachers and 21 students classified with emotional and behavior disorders (EBD) participated in an investigation of teacher effectiveness. Data collection included: video of teaching behaviors, interviews with teachers, and student surveys. The student survey identified characteristics of teacher effectiveness in general and of their teachers specifically. Results reinforced a framework of effective teaching behaviors: personal resources, teacher performance and teacher effectiveness. A significant correlation (p